CANNABIS AND MALE FERTILITY : A SYSTEMATIC REVIEW - Ayyasy, M. Zhafran (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Cannabis is a class of psychoactive substances derived from Cannabis sativa or Cannabis indica that can induce euphoria in the user. Cannabinoids are the term used to refer to the active component of cannabis, which contains 400 active compounds. DSM criterion 5 characterizes cannabis use disorder. Cannabis is the most commonly used illicit substance worldwide. The annual prevalence of cannabis abuse ranges from 2.9% to 4.3% of the global population aged 15 to 64. Cannabis sativa, Cannabis indica, and Cannabis ruderalis are the three varieties of cannabis. These three cannabis varieties contain varying amounts of tetrahydrocannabinol (THC). The THC content of Charas and hashish ranges between 7% and 14%. Cannabis and Sinsemilla are found in female shoots with an average THC concentration of 4-5% (rarely >7%). Low-grade Bhang preparations are derived from the 1% THC-containing residue of desiccated plants. Hashish oil, a concentrated liquid extracted from hashish distilleries, contains between 15 and 70 percent THC. Semen parameters provide the strongest evidence of cannabis-induced alterations in male fertility. Cannabis reduces sperm count and concentration, induces abnormalities in sperm morphology, reduces sperm motility and viability, and inhibits capacitation and fertilizing capacity, according to research.